Information fusion and geographic information systems towards the digital ocean - Popovich, Vasily (Lecture Notes in Geoinformation and Cartography, 2011)
The Workshop Proceedings reflect problems of advanced geo-information science as far as they are specifically concerned with the maritime environment at large. The Proceedings incorporate papers presented by leading scientists researching in the considered professional area and by practitioners engaged in GIS and GIS applications development.  They pay close attention to the problems of scientific and technological innovations and the ensuing opportunities to make seas safer and cleaner. Furthermore, they periodically measure the ground covered and new challenges with respect to economic and shipping trends as related to Artificial Intelligence; GIS ontologies; GIS data integration and modelling; Underwater acoustics; GIS data fusion; GIS and corporate information systems; GIS and real-time monitoring systems; GIS algorithms and computational issues; Novel and emerging marine GIS research areas; Monitoring of maritime terrorist threat; Maritime and environmental GIS; Navigation-based and maritime transportation GIS; Human factors in maritime GIS; Coastal and environmental GIS.